EXPLORING STUDENT PERCEPTIONS OF SYNCHRONOUS, ASYNCHRONOUS, AND BLENDED LEARNING APPROACHES: AN INVESTIGATION STUDY ON EDUCATIONAL GOALS - Mulbar, Usman; Ismiyati, Nur; Zaky, Ahmad (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract: This study aims to explore student perceptions of learning with synchronous, asynchronous, and blended learning approaches. This study is quantitative descriptive research with a survey approach, which refers to the National Student Survey, consisting of 9 aspects: teaching methods, learning opportunities, assessment and feedback, academic support, organization and management, learning resources, learning communities, student opinions, and overall satisfaction. The participants were 120 students. The results showed that the mean scores of the synchronous approach were higher on teaching methods, learning opportunities, assessment and feedback, learning resources, and overall satisfaction aspects; blended learning on organization and management, learning community, and student opinion aspects; and had the same on academic support aspect. Although the findings are limited, they can be used to inform and improve future pedagogical approaches in optimizing more effective student learning. Recommendation for further research requires guidance in designing learning by collaborating asynchronously and synchronously by paying attention to these aspects. Abstrak: Tujuan dari penelitian ini untuk mengeksplorasi persepsi mahasiswa tentang pembelajaran dengan pendekatan pembelajaran sinkronous, asinkronous dan blended learning. Penelitian ini menggunakan deskriptif kuantiatif dengan pendekatan survei yang merujuk pada National Student Survey, terdiri dari 9 aspek: metode pengajaran, peluang belajar, penilaian dan umpan balik, dukungan akademik, organisasi dan manajemen, sumber belajar, komunitas belajar, pendapat mahasiswa, dan kepuasan secara menyeluruh. Sebanyak 120 mahasiswa yang berpartisipasi. Hasil penelitian menunjukkan bahwa nilai rata-rata pendekatan sinkronous lebih tinggi pada aspek metode pengajaran, kesempatan belajar, penilaian dan umpan balik, sumber belajar, dan kepuasan secara keseluruhan, dan blended learning pada aspek organisasi dan manajemen, komunitas belajar, dan pendapat mahasiswa, dan keduanya sama pada aspek dukungan akademik. Walaupun temuan terbatas akan tetapi dapat digunakan untuk menginformasikan dan meningkatkan pendekatan pedagogis masa depan dalam mengoptimalkan pembelajaran mahasiswa yang lebih efektif. Rekomendasi penelitian selanjutnya perlu adanya panduan dalam merancang pembelajaran dengan mengkolaborasikan asinkronous dan sinkronous dengan memperhatikan aspek-aspek tersebut.